The dopamine system from an evolutionary perspective - Grillner, Sten; Robertson, Brita (Handbook of Behavioral Neuroscience, 2025)
The action and distribution of the dopamine systems are presented in an evolutionary perspective. In both vertebrates and invertebrates, the action of dopamine is exerted through D1-like and D2-like receptors. In all vertebrates, dopamine neurons are located in structures homologous to a substantia nigra pars compacta (SNc) and from amphibians to primates also in the adjacent ventral tegmental area (VTA). The afferent and efferent dopamine projections of the SNc/VTA are similar in all vertebrates investigated. In addition, dopamine neurons are present in the olfactory bulb and in different locations within the hypothalamus, distributed in a virtually identical manner, from lampreys to primates. In vertebrates, protovertebrates, arthropods (fruit fly), and Caenorhabditis elegans dopamine is present and associated with learning (reward, aversion) and motor actions. Dopamine neurons come in different flavors and genetically defined subtypes are identified with specific projections to the different target areas in the forebrain and midbrain.